Key Distribution and Security Frameworks in Wireless Sensor ‎Networks Based on Dynamic Stepwise Tiny Encryption ‎Algorithm - Karthik, M.; Balakrishna , R. (International Journal of Basic and Applied Sciences, 2025)
Data security and user privacy has become increasingly important in our daily lives. Sensitive information is stored in different devices like ‎a smartphone, personal computers, laptops, etc. However, most of the user devices are not adequately protected, and malicious threats ‎against sensitive information are growing rapidly. In this modern era, the realization of the importance of security and privacy has made ‎security a global concern for everyone. The recent years have witnessed that the Internet of Things-(IoT) has become a reality where a ‎number of embedded objects and devices are interconnected to monitor the environment and also it has a potential feature of human-machine ‎interaction. In the next few decades, it is expected that IoT becomes the major driver of productivity and growth in every aspect of human ‎life. The wireless sensor networks-(WSN) act as a backbone for the IoT-ecosystem, where connectivity between several sensor nodes and ‎the internet is established to accomplish different tasks. WSN has multiple security constraints. Therefore, traditional network security ‎mechanisms cannot be directly implemented in the sensor network. It is essential to first understand WSN security constraints for designing ‎an energy-saving security technique. The proposed system provides a novel solution in which a very lightweight encryption technique is ‎applied to ensure multiple-layers of security. The system allows only valid sensor nodes through authentication using signatures. Both ‎forward and backward secrecy is ensured by building a dynamic network topology. The proposed system can be claimed to be cost-‎efficient. It offers comprehensive security features with lightweight encryption and a hop-2-hop message authentication mechanism in ‎WSN, which does not depend on any complex operations. Therefore, the proposed scheme is energy-efficient, secure, and suitable for time-‎sensitive real-world applications.